Analysis of Farmers' Satisfaction Level with the Performance of Agricultural Extension Agents (Case Study of Rantau Kasai Village, North Tambusai Subdistrict, Rokan Hulu Regency, Riau Province) - Sischa Febriani Yamesa Away; Laily Fitriana; Heti Heniarsih Br. Nasution (Open Global Scientific Journal, 2022)
Extension is a form of effort to educate and improve the lives of Indonesian citizens. In particular, the performance of agricultural extension agents is a measurement of the success of agricultural extension activities. This is certainly inseparable from the quality of human resources that available in supporting the implementation of agricultural extension activities. Rantau Kasai Village is one of the villages located in North Tambusai Subdistrict, Rokan Hulu Regency, Riau Province, which based on data from the Agricultural Extension Agency has seven farmer groups and the majority of the population are farmers. Agricultural extension in Rantau Kasai Village has been carried out, but the level of farmers’ satisfaction with the performance of extension agents needs to be deeply investigated. This research was conducted using the survey method. Sampling using the Slovin technique obtained a sample size of 84 respondents from 174 farmers. The results showed that the level of conformity shows the highest level (100%), namely at the attribute of extension agents’ understanding to the specific needs of farmers and their groups. The results of Importance Performance Analysis (IPA) reveal that quadrant III (Low Priority) is the dominant quadrant containing 12 attributes of agricultural extension agents’ performance. The result of the Customer Satisfaction Index (CSI) analysis shows a value of 81.19% or 0.8119, which is classified into the “very satisfied” category, meaning the farmers are very satisfied with the performance of agricultural extension agents.